Analisis Penerapan Manajemen Pengendalian Vektor Demam Berdarah Dengue (DBD) di Lingkungan 19 Kelurahan Belawan Bahagia - Nanda, Meutia; Berutu, Azijah Nur Ismail; Ash-shiddiq, M. Daffa; Berutu, Winta Oktavia (IAI Nasional Laa Roiba Bogor, 2023)
There are 5 dengue cases in 19 neighborhoods with 1 death rate in 2022. This study aims to determine the application of DBD vector control management in Environment 19 of Belawan Bahagia Village.This is qualitative research using the Descriptive Analytics method, with 3 informants with criteria that have been set by the researcher. The result of this study is that there is no program yet This is qualitative research using the Descriptive Analytics method, with 3 informants with criteria that have been set by the researcher. The result of this study is that there is no vector control program that causes Dengue Hemorrhagic Fever (DHF) biologically, physically, and chemically in Environment 19 of Belawan Bahagia Village.The conclusion of this study is that the management of vector control that causes Dengue Hemorrhagic Fever (DHF) has not been carried out properly. It is necessary to carry out maximum vector control of the causes of dengue fever in the environmental area 19 Belawan Bahagia Village to prevent dengue health problems. Keywords: Dengue Hemorrhagic Fever, Ward 19, Belawan Bahagia